2010
DOI: 10.1152/ajpcell.00449.2009
|View full text |Cite
|
Sign up to set email alerts
|

High concentrations of HGF inhibit skeletal muscle satellite cell proliferation in vitro by inducing expression of myostatin: a possible mechanism for reestablishing satellite cell quiescence in vivo

Abstract: Skeletal muscle regeneration and work-induced hypertrophy rely on molecular events responsible for activation and quiescence of resident myogenic stem cells, satellite cells. Recent studies demonstrated that hepatocyte growth factor (HGF) triggers activation and entry into the cell cycle in response to mechanical perturbation, and that subsequent expression of myostatin may signal a return to cell quiescence. However, mechanisms responsible for coordinating expression of myostatin after an appropriate time lag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 101 publications
7
83
0
Order By: Relevance
“…Similarly, knockdown of Numb in MDCK cells destabilizes E-cadherin-based cell adhesion and potentiates sensitivity to hepatocyte growth factor (HGF) (74,75). Intriguingly, we recently reported that high concentrations of HGF inhibit satellite cell proliferation by inducing Mstn (76). This observation opens the possibility that HGFdependent signaling could link Numb to Mstn expression.…”
Section: Discussionmentioning
confidence: 94%
“…Similarly, knockdown of Numb in MDCK cells destabilizes E-cadherin-based cell adhesion and potentiates sensitivity to hepatocyte growth factor (HGF) (74,75). Intriguingly, we recently reported that high concentrations of HGF inhibit satellite cell proliferation by inducing Mstn (76). This observation opens the possibility that HGFdependent signaling could link Numb to Mstn expression.…”
Section: Discussionmentioning
confidence: 94%
“…Even the concentration of a particular growth factor and its interaction with other factors, e.g. HGF and myostatin, may be crucial for its effect on satellite cells (Yamada et al 2010). …”
Section: Satellite Cell Contribution To Skeletal Muscle Regenerationmentioning
confidence: 99%
“…The temporal reimmergence of the satellite cell quiescent state occurring after extensive repair of the myofibers may be related to a niche-based signaling mechanism. Recently, HGF 45 and Ang1, 30 have been implicated as quiescence-inducing, ligand derived-growth factors. The Ang1/Tie-2 signaling cascade also regulates quiescence and self renewal of the HSCs, 46 suggesting certain conservation for quiescence regulation, at the level of RTK signaling and niche-based regulatory mechanisms.…”
Section: Muscle Satellite Cellsmentioning
confidence: 99%